Variasi Latihan Groundstroke Forehand & Backhand Dalam Bentuk Games Untuk Atlet Junior Tenis Lapangan - Arifianto, Irfan; Raibowo, Septian; Jatra, Rices (Jurnal MensSana, 2021)
Tennis is one of the most popular sport branches which very attractive to people nowadays. However, the varied fundamental techniques have been burden for this sport as it is hard to learn in short period of time. Groundstroke forehand and groundstroke backhand are the two among basic techniques in order to prepare and create the accomplished athlete. In training program, variety innovations are needed, hence the exercise situation become more interesting and also avoid such boredom. The convenient training model for children development is based on play and stay concept. The research method used is development. The final product of this research is the variety of training which emphasizes on groundstroke forehand & backhand exercise in the form of video by using games concept for junior tennis athlete. In tennis, presenting the training portion through playing concept to junior athlete (6-12 years old) is the exact option, because in that age, giving the proficiency and understanding of movement is easier to build. Delivering the training program within the support of technology will make it more focused and on target.